Holocene landscape evolution and its interaction with human activities in the southern piedmont of Taihang Mountain, Central China - Zhang, Xiaohu; Yang, Shugang; Lu, Peng; Li, Yaping; Chen, Panpan; Xia, Zhengkai (Frontiers in Plant Science, 2022)
Piedmont zones have been witnessing intensive human activities since ancient times. However, it remains unclear when it comes to the environmental mechanism for early humans exploiting piedmont zones. Here we present a case study about the interactions between early human activities and landscape evolution in the piedmont of Taihang Mountain, an area with prominent ecological and cultural significance in Chinese history. Based on chronological and pollen analyses, we reconstruct the regional landscape evolution in the Fengtougang (FTG) site of southern Taihang Mountain during the Holocene. The results show that the area has been dominated by terrestrial plants since the late Longshan culture (4000 BP), including a large number of Pinus, Artemisia, Spiraea, and Gramineae, a few Cattails, and some other aquatic herbs. During the early history (4000-2000 BP), there is a combination of Pinus, Artemisia, Spiraea, Compositae, and Selaginella Chinensis, with a few aquatic plants. Since the late history (500 BP), the Chinese selaginella, Pinus, Selaginella, and Sedge families dominate, with no aquatic plant pollen found. Combining the detailed geoarchaeological survey, grain size analysis, and magnetic susceptibility analysis, we demonstrate that there should be a landscape of extensive floodplain during the early-middle Holocene (10000-4000 BP). During the late Longshan culture (about 4000 BP), the study area should be dominated by a landscape of sparse forest grassland with interlacing rivers and lakes. With river downcutting and watercourse fixation since the late Longshan culture, the flooded area massively shrinks, providing suitable habitat for human settlement. From then on, human activities begin to move to the study area on a large scale, followed by continuous cultural development and thriving early civilization.